TRANSMISI TRANSGEN (PhGH) DAN PERFORMA PERTUMBUHAN IKAN LELE (Clarias gariepinus) TRANSGENIK F-3 Transmission of Transgene (PhGH) and Growth Performance Catfish (Clarias gariepinus) Transgenic F-3 - Sultan Akbar Habibullah; Zulkifli Nasution; Yunasfi Djayus; Huria Marnis (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Fish increasing in aquaculture production requires the fulfillment of the need toaccelerate the productivity. Transgenesis technology with the introduction of transgenes(PhGH) can be performed to produce the fish that grow faster and has better performance.Transgene detection was performed using the PCR (Polymerase Chain Reaction) method andelectrophoresis using seed of transgenic catfish F-3. Furthermore, the observation of theperformance of catfish transgenic F-3 by measuring the rate of fertilization (the number offertilized eggs / total eggs), hatchability rate (the number of hatched eggs / number offertilized eggs), the survival rate (the number of early fish / amount of fish end), theperformance of growth (weight average transgenic F-3 / weight average non-transgenic) andfeed efficiency (absolute growth rate / daily feed intake). Results indicate that thetransmission rate ranged from 5-75% with an average transmission in the female transgenikF-2 by 2.5% (15/600) and 14.4% (75/520) in the male transgenik F-2. Weight growth rate of1.7 fold compared with non-transgenic. F-3 transgenic catfish has a degree of fertilization0.37% smaller and has a hatching 4% higher than the non-transgenic. Transgenic catfish feedefficiency higher than non-transgenic This shows that transgenic catfish has betterperformance compared with non-transgenic.Keywords: Transgenic catfish F-3, transgene (PhGH), transmission, Polymerase ChainReaction, growth performance